Social marketing and public health theory and practice - French, Jeff.; Blair-Stevens, Clive; McVey, Dominic; Merritt, Rowena (Oxford : Oxford University Press, 2010)
Social marketing uses established commercial marketing tools and principles to influence behaviour change, and is increasingly becoming a major tool in health promotion. This book provides an international account of the theory and practice behind social marketing.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Health planning; Social marketing; Communication in public health; Health promotion